Determinants of National Health Insurance (JKN) Coverage in Indonesia: Evidence from the 2023 Health Profile (Universitas Muhammadiyah Yogyakarta, 2025)
The National Health Insurance (JKN) is one of the Indonesian government’s strategic programs aimed at achieving universal healthcare coverage in Indonesia. Despite the growing number of participants, regional inequities in JKN coverage persist. The purpose of this study is to examine the factors that significantly determine the coverage level of active participation in the JKN in Indonesia, based on data available per province. The data used are secondary data from the Indonesian Health Profile in 2023, and multiple regression analysis was employed on data from 34 provinces in Indonesia. The independent variables are the percentage of poor persons in Indonesia, Contribution Assistance Recipients or participants of PBI, the ratio of the number of healthcare centers to the number of sub-districts, and the number of physicians per 100,000 persons in Indonesia. The findings disclosed that the percentage of persons in poverty had a negative effect on JKN coverage. In contrast, the effect of PBI participants and the number of physicians had a significantly positive effect on JKN coverage. The effect of healthcare centers was less consistent with the hypothesis of enhanced coverage, establishing that while the expansion of healthcare centers was not a guaranteed factor in improving healthcare coverage in JKN, distributing healthcare evenly can still yield relatively good coverage for Indonesian society in general.